An efficient and interactive android-based neighborhood management - Junianto, Haris; Saputra , Dhanar Intan Surya; Saputro, Rujianto Eko (Association for Scientific Computing Electrical and Engineering, 2024)
This research aims to design and develop a prototype Android-based Neighborhood Association management information system application using the Agile approach to assist Neighborhood Association administrators in real-time administrative processes and information dissemination. The Agile approach was selected to enhance flexibility and responsiveness in application development, enabling adjustments to potential user needs and changes that may occur during the development process. The application is expected to improve service quality and governance transparency at the Neighborhood Association level while facilitating residents' access to information and interaction with Neighborhood administrators. The application development process employs the Agile approach, involving the development team in iterative cycles to meet user requirements. Research results demonstrate the achievement of research objectives, with the application capable of managing resident data, Neighborhood Association finances, event scheduling, and Neighborhood Association news. The Agile approach used in the application's development provides the flexibility needed to adapt to changing user requirements, offering a solution to the challenges faced by Neighborhood Association administrators in performing their duties. This aligns with Agile principles, emphasizing user collaboration and responsiveness to changes.